2017
DOI: 10.1111/liv.13509
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of body composition and definition of sarcopenia in patients with alcoholic cirrhosis: A computed tomography based study

Abstract: Compensated ALC have increased adiposity and relatively preserved muscularity but decompensation leads to loss of both muscle and fat mass. Prevalence of sarcopenia, based on derived ethnic cut-offs was 12.8%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
2
46
2
Order By: Relevance
“…Indeed, cirrhosis is a state of accelerated starvation that is believed to be responsible for the reduced skeletal and adipose tissue mass. 1,8,42 This study, in a large group of patients, confirms the differential response between subcutaneous and visceral fat after TIPSS placement, which has been suggested in previous studies. 1,34 Moreover, our study provides original data on the evolution of fat distribution and suggests that it is more likely than sarcopenia to rapidly change in response to slight or temporary HVPG variations.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, cirrhosis is a state of accelerated starvation that is believed to be responsible for the reduced skeletal and adipose tissue mass. 1,8,42 This study, in a large group of patients, confirms the differential response between subcutaneous and visceral fat after TIPSS placement, which has been suggested in previous studies. 1,34 Moreover, our study provides original data on the evolution of fat distribution and suggests that it is more likely than sarcopenia to rapidly change in response to slight or temporary HVPG variations.…”
Section: Discussionsupporting
confidence: 88%
“…Currently, CT is considered one of the most accurate methods for analyzing quantitative and qualitative changes in body composition, especially when investigating skeletal muscle mass and distinguishing adipose tissue in different body compartments (12,20). A dedicated computer software is required to quantify and determine components in different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have used abdominal CT to quantify body composition parameters in a variety of clinical situations, such as renal (11) and hepatic (12,13) disease, obesity (3) and cancer (14)(15)(16). Different software programmes have been used to perform these body composition analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, muscle fatty degeneration and decrease of muscle mass measured by CT occur predominantly in advanced cirrhosis [ 13 , 16 ]. In fact, in a study by Benjamin et al, the prevalence of sarcopenia identified on CT measures was 12.8% in patients with alcoholic liver cirrhosis [ 39 ]. Furthermore, the authors observed significant differences regarding muscle area and muscle index between healthy persons and patients with alcoholic liver cirrhosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%